Correlation Analysis between Helicobacter pylori Infection Status and Tumor Clinical Pathology as Well as Prognosis of Gastric Cancer Patients - Jing WANG; Xiaofeng LIU (Tehran University of Medical Sciences, 2018)
Background: We aimed to investigate the correlation between Helicobacter pylori infection and the development and prognosis of gastric cancer. Methods: Retrospective analysis was used to collect 120 paraffin-embedded specimens and 42 paracancerous specimens of gastric cancer patients archived in Department of Pathology, Weihaiwei People's Hospital from 2010-2012. All patients with gastric cancer were followed for 5 years. Real-time fluorescent quantitative PCR was used to detect the relative H. pylori infection in gastric cancer tissues and paracancerous tissues. The relationship between clinicopathological parameters and H. pylori relative infection was analyzed. Kaplan-Meier was used for survival analysis. Results: The relative amount of H. pylori infection in gastric cancer tissues was significantly higher than that in paracancerous normal tissues (P<0.001). The relative H. pylori infection was related to tumor size, lymph node metastasis, clinical stage, and depth of invasion (P<0.05). The 1-, 3-, and 5-year survival rates of gastric cancer patients were negatively correlated with the relative H. pylori infection. The relative H. pylori infection, age, tumor size, lymph node metastasis, distant metastasis, clinical stage and depth of invasion were positively correlated with the prognosis of patients with gastric cancer. Conclusion: The relative H. pylori infection and clinical stage of patients could increase the risk of death in gastric cancer patients. H. pylori is one of the independent risk factors for the progression and prognosis of gastric cancer. It is also an index to evaluate the development process and prognosis of gastric cancer.